SUPPLEMENTARY LABORATORY INVESTIGATIONS OF MODERN PLASTIC-POLYMER FISHPLATES FOR RAIL JOINTS - Nemeth, A.; Fekete, I.; Szalai, S.; Fischer, S. (Science and Transport Progress, 2019)
Purpose. The authors’ goal is to determine the behavior of insulated rail joints with polymer-composite fishplates without glueing in the consideration of dynamic loadings regarding to own laboratory tests. In this paper they introduce the applied measurement opportunities. Methodology. Dynamic (fatigue) bending tests were performed by insulated rail joints assembled with plastic-polymer fishplates. The special laboratory measurements are related to digital picture/video measurement technique and assessment method executed by GOM hardware and software, as well as computer tomography according to laboratory bending tests. Findings. In previous papers the authors published the results of glued-insulated rail joints, in this period they continued their research with the investigation of rail joints with plastic-polymer fishplates without glueing. They tested two different types of rail fishplates made of plastic-polymer material. For the rail joints with fishplates but without glueing, the authors applied special measurement techniques by GOM products (Tritop, Aramis) that enable high precision digital measurement techniques with spectacular visualization results. The computer tomography records ensure the opportunity to be able to receive information about inner crackings and faults of plastic-polymer fishplates, with also high precision measurements. The assessment method has to be developed for these specific measurement methodologies to be able to compare the results and define scientific statements. Originality. Up to now any researcher and research group have been dealing with insulated rail joints with special plastic-polymer fishplates without glueing applied mentioned special techniques, no one determined the exact deterioration process of these joints, as well as the crack growing phenomenon in the cross section of the fishplates. Practical value. The research team of the authors had the possibility to see into the details of glass-fibre reinforced resin bonded plastic fishplates during laboratory tests, as well as they publish timely information in the consideration of their laboratory tests’ results. This result can be applied in railway engineering at all stages: design, construction, maintenance&operation in the future.